Large-scale periodic velocity oscillation in the filamentary cloud G350.54+0.69. Issue 1 (16th May 2019) - Liu, Hong-Li; Stutz, Amelia; Yuan, Jing-Hua
Abstract: We use APEX mapping observations of 13 CO and C 18 O (2-1) to investigate the internal gas kinematics of the filamentary cloud G350.54+0.69, composed of the two distinct filaments G350.5-N and G350.5-S. G350.54+0.69 as a whole is supersonic and gravitationally bound. We find a large-scale periodic velocity oscillation along the entire G350.5-N filament with a wavelength of ∼1.3 pc and an amplitude of ∼0.12 km s −1 . Comparing with gravitational-instability-induced core formation models, we conjecture that this periodic velocity oscillation could be driven by a combination of longitudinal gravitational instability and a large-scale periodic physical oscillation along the filament. The latter may be an example of a magnetohydrodynamic transverse wave. This hypothesis can be tested with Zeeman and dust polarization measurements.